2010
DOI: 10.1016/j.econedurev.2009.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Does price matter? Overseas students in UK higher education

Abstract: a b s t r a c tThis paper explores the determinants of the choice of UK universities by overseas undergraduate applicants. We use data on overseas applicants in Business Studies and Engineering from 2002 to 2007, to 97 UK universities. Estimating using a Hausman-Taylor model to control for the possible correlation between our explanatory variables and unobservable university-level effects, we find that the fees charged may influence the application decision of some students, but that any relationship between l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 25 publications
1
49
0
4
Order By: Relevance
“…Lowe () found that Chinese students regarded the ‘opportunity to improve my English level’ as an important determinant when deciding to study a UG B&M programme at a UK university. In addition to ‘developing English skills’, Soo and Elliott () identified ‘high entry requirements’ and ‘the subject ranking’ important in Chinese students' choice of a UG B&M programme; however, these variables were not as influential for the choice of an engineering programme. Other respondents were interested in opportunities for living and working in the destination country following graduation (generally referred to as ‘future migration opportunities’): if they are motivated by the desire to live and work in the host country, the immigration policies in Australia and Canada are amongst the most favourable, and are key factors in attracting students to these countries.…”
Section: Empirical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lowe () found that Chinese students regarded the ‘opportunity to improve my English level’ as an important determinant when deciding to study a UG B&M programme at a UK university. In addition to ‘developing English skills’, Soo and Elliott () identified ‘high entry requirements’ and ‘the subject ranking’ important in Chinese students' choice of a UG B&M programme; however, these variables were not as influential for the choice of an engineering programme. Other respondents were interested in opportunities for living and working in the destination country following graduation (generally referred to as ‘future migration opportunities’): if they are motivated by the desire to live and work in the host country, the immigration policies in Australia and Canada are amongst the most favourable, and are key factors in attracting students to these countries.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Other respondents were interested in opportunities for living and working in the destination country following graduation (generally referred to as ‘future migration opportunities’): if they are motivated by the desire to live and work in the host country, the immigration policies in Australia and Canada are amongst the most favourable, and are key factors in attracting students to these countries. By contrast, this was of much less importance to students who had chosen the UK (Lord and Dawson, ; Binsardi and Ekwulugo, ; Lowe, ; Rawson, ; Soo and Elliott, ), or the USA (McMahon, ). Linked to these studies are those that deal with the ease of psychological adjustment to the host country: such as undertaken by Burns () or Spencer‐Oatey and Xiong ().…”
Section: Empirical Studiesmentioning
confidence: 99%
“…One of the few multivariate studies to examine the influence of subject-department rankings is Soo and Elliott (2010). Applications from non-European Union (EU)/non-home domiciled students to business study degree courses are found to be sensitive to subject-specific rankings, but not their equivalents applying for engineering subjects.…”
Section: Previous Literaturementioning
confidence: 99%
“…The students returning to their homes after graduating, continue the positive relationship with the countries they study. This case has a positive effect upon the political, social, cultural and commercial relations between the two countries (Barber and Morgan, 1987;Altbach, 1989;Altbach, 1998;Bevis, 2002;Harrison, 2002;Saxenian, 2005, Slaughter andRhoades, 2004;Harzing, 2004;Naidoo, 2006;Marcottea, Desrochesb and Poupart, 2007;Soo and Elliott, 2010;NAFSA, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…This situation shows that tuition fee is not a stand-alone factor that impacts student preferences (Mazzarol and Soutar, 2002;Pimpa, 2003;Maringe, 2006;Maringe and Carter, 2007;Phang, 2013). Nevertheless international students consider tuition fees while comparing equivalent qualifications in terms of quality and training facilities (Naidoo, 2007;Soo and Elliott, 2010).…”
Section: The Cost Of International Educationmentioning
confidence: 99%